Strengthening the judicial system through digital transformation - Rania Laamrani El Idrissi; Samira BENBOUBKER (International Journal of Scientific Research and Innovative Studies, 2025)
The digital transformation of the judicial sector represents a major global shift aimed at modernizing procedures, improving accessibility, and enhancing transparency. In Morocco, recent legislative reforms have introduced various digital tools into the judicial system, making justice more accessible and accelerating judicial processes. This article examines the key legislative provisions adopted, relevant case law, and the associated challenges and benefits of digitizing Morocco’s judiciary. The objective is to highlight how these changes are reshaping judicial administration and influencing court decisions. Keywords: Digitalization, public administration, legal framework, judicial sector, Moroccan law. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/453